2023
DOI: 10.1088/2752-5295/acfa1b
|View full text |Cite
|
Sign up to set email alerts
|

Record-breaking and unprecedented compound hot and dry summers in Europe under different emission scenarios

Alessandro Dosio,
Jonathan Spinoni,
Mirco Migliavacca

Abstract: After analysing observed summer compound hot and dry (CHD) events over Europe from 1950 to 2022, we employ a large ensemble of high-resolution regional climate model simulations to investigate CHD events under different emission scenarios.
By the end of the century, even under a low-emission scenario, model results show a likely increase in the frequency and extension of CHD events over most (60%) of Europe. In particular, the fraction of land projected to be hit once every two years nearly doubles (at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…Similar conclusions for the European region are reflected in [2][3][4]. Based on the results of studies of forecast estimates [5], it was found that even in a low-emission scenario, a likely increase in the frequency and spread of heat and drought events in most of Europe is expected (60%). There are similar works for African countries [6][7][8][9] and Asia [10][11][12].…”
Section: Introductionsupporting
confidence: 53%
“…Similar conclusions for the European region are reflected in [2][3][4]. Based on the results of studies of forecast estimates [5], it was found that even in a low-emission scenario, a likely increase in the frequency and spread of heat and drought events in most of Europe is expected (60%). There are similar works for African countries [6][7][8][9] and Asia [10][11][12].…”
Section: Introductionsupporting
confidence: 53%
“…Our findings underscore the uncertainties inherent in model projections of the SAOD-rainfall relationship in the context of climate change. Because of the strong impacts of the SAOD, any shifts in this relationship with regional rainfall could trigger changes with far-reaching socioeconomic consequences (Almazroui 2020, Dosio et al 2023. Further studies focusing on the realistic models identified in this study are needed to investigate such future impacts to guide societal adaptation planning.…”
Section: Discussionmentioning
confidence: 97%